Biochemical Characterization and 16S rRNA Sequencing of Few Lipase-Producing Thermophilic Bacteria from Taptapani Hot Water Spring, Orissa, India. (22nd March 2011) - Bisht, Satpal S.; Panda, Amrita K.
Abstract : Three lipase-producing thermophilic bacteria (AK-P1, AK-P2, and AK-P3) were isolated from the Taptapani hot water spring in Orissa, India. The crude extra cellular lipases from cell-free culture supernatant were reacted in an olive oil mixture, and their lipolytic activities were compared. Identification of the bacteria was carried out using biochemical tests, 16SrRNA sequencing and sequences submitted to NCBI GenBank. Strain AK-P3, exhibited the highest lipolytic activity of 5.5 U/mL was identified as Porphyrobacter sp. The lipolytic activities of strains AK-P1 and AK-P 2 were 4.5 U/mL and 3.5 U/mL, respectively. Strains AK-P1 and AK-P2 were identified as Acinetobacter sp. and Brevibacillus spp. The GenBank accession numbers of the 16S rRNA gene sequences determined in this study for the strains AK-P1, AK-P2, and AK-P3 are HM359120, HM359119, and HM359118, respectively.